Bayesian 14C analysis, formation processes, and accumulation rates of the Prisoners Harbor shell midden and village complex, Santa Cruz Island, California. (September 2015) - Jew, Nicholas P.; Rick, Torben C.; Glassow, Michael A.; Arnold, Jeanne E.
Abstract: The Prisoners Harbor site (CA-SCRI-240), one of the largest sites on California's Channel Islands and the likely location of the Chumash village Xaxas, played a key role in regional models of emergent complexity and culture contact. Despite substantial excavation at the site, published research has focused on the most recent 500 years of the site's occupation, with comparatively little attention given to the 2–3 millennia preceding this. Here we focus on the formation and chronology of CA-SCRI-240 by presenting a Bayesian analysis of 36 radiocarbon dates from throughout the site's occupation. Comparing three suites of radiocarbon dates, we provide a revised chronology for CA-SCRI-240 and examine site formation processes, sediment deposition rates, and the implications our study holds for reconciling older radiometric dates with large analytical errors and higher precision accelerator mass spectrometry dates. Our analysis suggests that the earliest site occupation was 2750 cal BP, roughly 2000 years later than previously presumed. Sedimentation rates vary throughout the 5.7 m sequence. Deposits for the first 1000 years accumulated slowly followed by relative increase in accumulation rates in the uppermost occupation levels dating to historic times. Our study demonstrates the importance of Bayesian analysis for improving radiocarbon chronologies for large, multi-component sites. Highlights: Bayesian modeling of radiometric and high-precision AMS 14 C dates Analyses of sediment accumulation rates of a deeply stratified shell midden and village complex Bayesian analysis of 14 C dates and chronological hygiene greatly improves site chronologies. Refines chronology of key Late Holocene hunter–gatherer cultural developments